Hamka, Social Criticism and The Practices of Polygamy in Minangkabau - Saifuddin Herlambang (Graduate Program of Pontianak Institute of Islamic Studies, 2020)
The character and style of a text describes and reflects the cultural structure and nature of the author’s mind. This work attempts to describe social criticism and the interpretation of Hamka—the eminent Indonesian exegete—in the Al-Azhar (a fairly recent encyclopedic Quran commentary) of the verses which are legitimized as the verses of polygamy. This study finds that Hamka’s interpretation of “polygamy verses” is influenced by the social dynamics of his birthplace, Minangkabau. Hamka criticized religious and adat leaders for the polygamy tradition in Minangkabau. Paradigmatically, Hamka contributed a unique tradition in the dynamics of the interpretation of the Quran in Indonesia where interpretation becomes a social critic. This study reaffirmed the statements that the contestation in interpreting texts is a reflection of social and political contestation and not merely theoretical contestation and that each product of text interpretation expresses empirically the socio-political conditions of the interpreters. This work offered the idea that the interpretation of the Quran with a social approach is to voice criticism of the application of the text to be an alternative to continue in contextualizing the Quranic messages.